Khawa Karpo: Tibetan Traditional Knowledge and Biodiversity Conservation - Glover, Denise M. (Ethnobiology Letters, 2014)
Review of Khawa Karpo: Tibetan Traditional Knowledge and Biodiversity Conservation. Jan Salick and Robert K. Moseley. 2012. Missouri Botanical Garden, St. Louis. Pp. 273. US55 (paperback). ISBN 978-1-935641-06-3.